The genetic spectrum features of 2261 Chinese children with epilepsy and intellectual disability - Nan Pang; Chen Chen; Lifen Yang; Ciliu Zhang; Xiaolu Deng; Li Yang; Leilei Mao; Fangyun Liu; Guoli Wang; Haolin Duan; Xiaole Wang; Fei Yin; et al. (BMC Medicine)
Abstract Background Epilepsy (EP) and intellectual disability (ID) are two highly correlated diseases that seriously impact neurodevelopment in children. Precision diagnosis of EP and ID remains challenging due to their clinical and genetic heterogeneity, necessitating a profound understanding of disease characteristics. Methods We provide a clinical and genetic landscape of 2261 Chinese patients performed chromosome microarray analysis (CMA) or next-generation sequencing to uncover causal copy number variants (CNVs) or single-nucleotide variants (SNVs). Patients were stratified into three groups: EP (374 cases), ID (863 cases), and EP + ID (1024 cases). Results We reported a 24.3% diagnostic yield from 496 causal CNVs and SNVs, including 182 novel variants, in which updated 33 previously reported VUS. Significant intergroup differences emerged: EP patients were predominantly caused by autosomal dominant SNVs, showing the highest rates of incomplete penetrance and family history. ID patients were more likely caused by CNVs and autosomal recessive SNVs, with the highest genetic heterogeneity. EP + ID patients displayed the earliest onset ages and highest diagnostic yields. We prioritized genes by diagnostic efficiency and revealed that X-linked SNVs disproportionately affected females, particularly in the EP + ID group, under current diagnostic paradigms. This real-world dataset informs genetic counseling, testing strategies, precision therapies, and long-term management for EP/ID. Conclusions The clinical and genetic profiles from this study provided a reliable baseline reference for diagnosing EP and ID.